Dementia handbook & resource guide (Grey House Publishing, Inc., 2020)
This new title is designed to bring together necessary and valuable information for the millions of individuals, family members, and caregivers affected by dementia. For those providing care and support to individuals with dementia, this resource provides easy-to-understand and helpful information about dementia and connects readers to many sources of support.